Seismic Fragility Assessment of Irregular High Rise Buildings using Incremental Dynamic Analysis - Bhandari, Avinash; Suwal, Rajan; Khawas, Aakarsha (Advances in Engineering and Technology: An International Journal, 2022)
The construction of high rise buildings is common in city areas. These buildings may be irregular because of aesthetics or other requirements. As Nepal lies in a seismically active region these irregular high rise buildings may not perform well during earthquakes. Two existing irregular high rise buildings are taken as case study buildings that had pre-existing torsion. Shear walls are added to the building at the required location to minimize torsion in the buildings. The objective of the study is to determine the performance of building with and without torsional irregularity. The seismic performance of all the buildings is carried out by taking seven pairs of ground motions using nonlinear time history analysis. These ground motions are scaled to the required intensity to develop incremental dynamic analysis (IDA) curve. These IDA curves are used to develop fragility curves to access the performance in the buildings. The result from the analysis showed that performance in one building improved by 35% and in another by 70% at the peak ground acceleration (PGA) of 0.35g.